2021
DOI: 10.1021/acs.jafc.1c03791
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Mellitus-Induced Changes in Proteomes and Glycated/Glycosylated Proteomes of Human Colostrum

Abstract: Gestational diabetes mellitus (GDM) not only has a bad effect on the development of infants but also causes variations in breastmilk composition. This study aims to investigate the changes in the protein profile of colostrum between mothers with GDM and healthy mothers (H) by sequential windowed acquisition of all theoretical fragment ion proteomics techniques. A total of 1295 proteins were detected, with 192 proteins being significantly different between GDM and H. These significantly different proteins were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In another study, a total of 1295 proteins were detected, 192 of which showed significantly different concentrations in the the two groups. These 192 proteins were associated with carbohydrate, pro-inflammatory, and lipid metabolism [36]. In addition, using the same technique, Klein et al found that the the concentration of free amino acids in colostrum and mature milk was not affected by GDM [21].…”
Section: Proteinmentioning
confidence: 98%
See 1 more Smart Citation
“…In another study, a total of 1295 proteins were detected, 192 of which showed significantly different concentrations in the the two groups. These 192 proteins were associated with carbohydrate, pro-inflammatory, and lipid metabolism [36]. In addition, using the same technique, Klein et al found that the the concentration of free amino acids in colostrum and mature milk was not affected by GDM [21].…”
Section: Proteinmentioning
confidence: 98%
“…Transitional milk is produced from 6 to 15 days postpartum, while mature milk is produced from 15 days postpartum to weaning [40,41]. Colostrum has been studied most frequently, with 23 published studies [12,13,14,15,16,18,19,20,21,22,23,24,25,27,28,29,30,31,32,34,35,36,39]. In contrast, the transitional milk stage has been the least studied, with only nine published studies [17,19,20,24,29,31,32,34,35].…”
Section: Collection Of Breast Milk Samplesmentioning
confidence: 99%
“…Maternal lifestyle, including smoking, BMI, gestational diabetes, and diet, has been shown to affect the composition of breast milk, and this interplay with infant health is an area of research that is gaining traction (26)(27)(28)(29)(30). Exercise is a behavioural factor that has received little attention in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Breastfeeding for at least 6 months reduced childhood fat deposition resulting from exposure to GDM in utero ( 9 ). Components (i.e., proteins, lipids, and carbohydrates) of human milk may rewrite the fetal “metabolic programming” induced by GDM in the early postpartum period, leading to a lower risk of future metabolic disease ( 10 12 ). A recent study revealed that the breastmilk microbiota composition was also influenced by GDM and these changes may contribute to the dynamics of the infants’ gut microbiota establishment ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Breastfeeding for at least 6 months reduced childhood fat deposition resulting from exposure to GDM in utero (9). Components (i.e., proteins, lipids, and carbohydrates) of human milk may rewrite the fetal "metabolic programming" induced by GDM in the early postpartum period, leading to a lower risk of future metabolic disease (10)(11)(12). A recent study revealed that Abbreviations: 1hPG, 1 h plasma glucose; 2hPG, 2 h plasma glucose; ARA, arachidonic acid; CER, ceramide; DAG, diacylglycerol; DHA, docosahexaenoic acid; FA, fatty acids; FPG, fasting plasma glucose; GDM, gestational diabetes mellitus; HC, head circumference; HCER, hexosylceramide; HDLC, high-density lipoprotein cholesterol; LC/MS, liquid chromatography-tandem mass spectrometry; LDLC, lowdensity lipoprotein cholesterol; MAG, monoacylglycerol; MUFA, monounsaturated fatty acids; NC, normal controls; OGTT, oral glucose tolerance test; OPLS-DA, orthogonal projections to latent structures-discriminant analysis; PC, phosphatidylcholine; PCA, principal component analysis; PE, phosphatidylethanolamine; PI, phosphatidylinositol; PUFA, polyunsaturated fatty acids; QC, quality control; PL, phospholipid; SM, sphingomyelin; T2D, type 2 diabetes; TAGs, triacylglycerols; TC, total cholesterol; TG, triglyceride; VIP, variable importance in the projection.…”
Section: Introductionmentioning
confidence: 99%